Analisis Penggunaan Metode Kontrasepsi pada Pasangan Usia Subur (PUS) di Provinsi Aceh Tahun 2016 - Andriani, Mutia; Anwar, samsul (Sriwijaya Journal of Medicine, 2018)
Family Planning Program (KB) has several objectives that is, among others, to control population growth rate, raise awareness raising and community participation through maturation of marriage age, control birth rate, develop family resilience, and improve family welfare to accomplish a small, happy and prosperous family. This study aims to determine whether there is a significant difference in the number of significant KB users between each method of contraception used by the Elderly Age Couple (PUS) and to know which contraceptive method is the most widely used in Aceh Province. The approach used in this study was a quantitative approach. The data used were secondary data obtained from BKKBN (National Family Planning Coordinating Board) of Aceh Province. Data analysis method used in this study was Analysis of Variance (ANOVA). Anova analysis shows that there is a significant difference in the number of KB users among the six contraceptive methods used in Aceh Province with p-value < 0.001. Furthermore, based on a further test of Tukey, it is known that injectable contraception method is the most widely used method of contraception in Aceh Province in 2016.